Novel concepts in HDL pharmacology - Remaley, A.; Norata, Giuseppe; Catapano, A. (2014)
High-density lipoproteins (HDL) are a target for drug development because of their proposed anti-atherogenic properties. In this review, we will briefly discuss the currently established drugs for increasing HDL-C, namely niacin and fibrates, and some of their limitations. Next, we will focus on novel alternative therapies that are currently being developed for raising HDL-C, such as CETP inhibitors. Finally, we will conclude with a review of novel drugs that are being developed for modulating the function of HDL based on HDL mimetics. Gaps in our knowledge and the challenges that will have to be overcome for these new HDL based therapies will also be discussed. © Published by Oxford University Press on behalf of the European Society of Cardiology 2014.